The mediating and moderating effect of psychological factor and salesperson personality on the relationship between cognitive factors and customer satisfaction among automobile users / Sarah Sabir Ahmad - Sabir Ahmad, Sarah (2019)
Customer satisfaction has been identified as the key performance indicator of a business and contributes to competitive advantage for the organization. Customer satisfaction changes over time and has been acknowledged as a crucial differentiator and key element to business strategies. Lack of customer satisfaction provide a massive impact on the retention of the organization. Due to lackluster customer services, technical glitches and low product quality and services, Proton faced a tremendous decline in sales and lost the market share it once owned. The customer seems to switch from preferring Proton cars to other manufacturers. A minimal amount of research has been done to identify the root, yet the gap still transpires. Therefore, the aim of this present study is first; to determine the influence of cognitive factors (marketing and technological) on customer satisfaction and secondly; to identify the mediating effect of psychological factor on the relationship of cognitive factors and customer satisfaction. Besides, this study also aims to identify the moderating effect of the salesperson personality style (Type A or B) on the said relationship. Since this study is a quantitative in nature, it employed the self-administered questionnaire method for data collection.